An Unusual and Rare Presentation of Pulmonary Aspergillosis: Endobronchial Aspergilloma - Mohammed Ali; Aisha Mujahid; Rahul Dadhwal; Abhay Vakil; Humayun Anjum; Salim Surani (Case Reports in Infectious Diseases)
Aspergillosis is a wide spectrum of the disease process that is caused by the fungus Aspergillus. Endobronchial aspergilloma is a very rare type of aspergillosis which is not yet included in the classification of aspergillosis. Due to its rare nature and a limited number of cases, there are no current treatment guidelines. Here we present the case of a 57-year-old female with an endobronchial aspergilloma. The patient was started on intravenous voriconazole and subsequently discharged on oral voriconazole.